Necrotizing fasciitis of the lower extremity caused by perforated sigmoid diverticulitis—a case report. Issue 8 (6th August 2018) - Kröpfl, Veronika; Treml, Benedikt; Scheidl, Stefan; Lanthaler, Monika; Nogler, Michael; Lorenz, Ingo; Friesenecker, Barbara; Fries, Dietmar; Pierer, Gerhard; Öfner-Velano, Dietmar
Abstract: Diverticulosis of the sigmoid colon is a common condition and occurs more often in elderly patients. A well-known complication is infection or even perforation which often requires surgery. Necrotizing fasciitis as a complication of perforated diverticulitis is very rare. Here, we present a case of a covered perforated diverticulitis in an immunosuppressed patient leading to life-threatening necrotizing fasciitis requiring extracorporeal membrane oxygenation. Either hematogenous or local dissemination via the inguinal canal seemed the most probable mechanism of leg infection leading to hip articulation.